A study of five cases of rheumatoid arthritis and one case of rheumatic fever with special reference to the etiology of rheumatoid arthritis - Merriweather, [unknown] (The University of Edinburgh, 1941)
1. I am indebted to Professor D. Murray Lyon end Professor D.M. Dunlop for permission to report these cases which were studied in their Wards at the Royal Infirmary. 2. It is obvious that little progress will be made in the treatment of Rheumatoid Arthritis until the question of Etiology is cleared up and for that reason I have laid most stress on that part of the study. At the same time the pathology, clinical features, treatment and prognosis are discussed quite fully. 3. The case of Rheumatic Fever is not entirely typical and is used to illustrate points of similarity and dissimilarity between the two conditions end the possible relationship between them. Consequently I have not gone into e detailed discussion of the various aspects of Rheumatic Fever. 4. It will become obvious on reading these cases that I have been searching for certain etiolcgical factors which I have particularly wanted to emphasise end the suspicion may arise that I have carefully selected cases which illustrate these factors. Actually the cases were taken in the order in which they came into the Wards and were, I think, the only cases of Rheumatoid Arthritis admitted to Wards 22, 23 end 24 during my two terms. This being so, the fact that certain etiological points are shown by several cases is of more significance than if I had hunted for cases which would show certain points in common.